Testing the Late Paleozoic Ice Volume Paradox in the Southernmost Paraná Basin, Brazil - (:unkn) unknown (My University, 2019)
The late Paleozoic ice age (LPIA; ~372-259 Ma) was the last complete transition from icehouse to greenhouse conditions on a fully vegetated Earth, making it a relevant analog for modern Earth systems. High frequency glacioeustatic fluctuation of ~100-200 m during the late Paleozoic are described by some authors in low paleolatitude basins and attributed to the orbitally-driven, waxing and waning of a massive (~20-35 x 106 km2) hypothetical ice sheet. This massive ice sheet is traditionally interpreted to have covered much of southern Gondwana for >100 m.y. Meanwhile, recent studies of high-paleolatitude glacial deposits imply a much more complex pattern of glaciation with distinct, smaller ice centers that persisted for Sedimentological and geochemical analyses of glacial deposits on the southernmost margin of the Paraná Basin indicate that the glacier covering this region was warm-based or polythermal and it experienced repeated fluctuations in ice-marginal positions during the Carboniferous. The glacial foreland was as a temperate, transitional, lacustrine to estuarine environment. Paleovalleys on the southern margin of the Paraná Basin were previously viewed as fjords that drained an ice center over northern Namibia, which is also thought to have supplied ice to the eastern Paraná Basin. Contradicting this hypothesis, these paleovalleys were found to be non-glacial in origin. Furthermore, the orientations of subglacial erosional features, paleocurrents, and glaciotectonic deformation structures from the southern Paraná Basin all support an unconfined lobe that advanced radially NNE and NNW out of Uruguay during the late Paleozoic. Therefore, at least two distinct ice centers are believed to have supplied sediment to the eastern and southern margins of the Paraná Basin. Detrital zircon (U-Pb) geochronology was used to assess the provenance of glacial sediments in the eastern Chaco-Paraná Basin (Uruguay) in order to determine the source region of the ice center that flowed N into the southern Paraná Basin. The detrital zircon samples indicate that glaciogenic sediments were derived from SE Uruguay, which was likely connected to the Cargonian highlands of southern Namibia and northern South Africa. This study supports the emerging view of LPIA glaciation, which purports that the glaciation consisted of multiple topographically controlled ice centers. The absence of glaciers on the southernmost Paraná Basin during the early Permian means that glaciation in southern Brazil does not correlate to widespread Permian glaciation in Africa. This is further evidence that late Paleozoic glaciation did not occur everywhere simultaneously. Thus, based on this study, the ice-volume paradox is most likely the result of over-estimates of glacioeustatic fluctuations.
Keywords: Brazil; Glacial; Late Paleozoic Ice Age; Parana Basin; Rio Grande do Sul Shield; Uruguay